Samemästerskapens uppkomst : Om idrott, inkludering och exkludering utifrån stats- och etnicitetsgränser - Lidström, Isak (Malmö högskola, Institutionen Idrottsvetenskap (IDV), 2017)
This article sheds light on the history of Sámi sport and focuses on the emergence of the Sámi Ski Championships in Sweden, a winter sport event founded in 1948 in which the Sámi, an indigenous people living in the north of Europe, compete against each other in cross-country skiing and other sports with roots in Sámi culture. The championships have had an important function in shaping a Sámi identity through sporting activities. Although competition and performance were prominent elements of the Sámi Ski Championships in the early years, a superior aim was to create a space where Sámi could meet and socialize, and where the Sámi cohesion could be strengthened. However, in this study it becomes apparent that the event was not only an arena for inclusion but also for exclusion. During the first decades, only Sámi residing in Sweden had the right to participate in the championships, although the Sámi live in an area that stretches across the state borders of Sweden, Norway, Finland and Russia (formerly the Soviet Union). However, the exclusion went even further. In fact, only those (the Sámi) who had the right to carry out reindeer husbandry were allowed to compete, thereby excluding a major part of the Sámi population in Sweden. The article therefore provides an analysis of how a Sámi identity was constructed at the Sámi Ski Championships from 1948 to 1959 – a construction entangled with cultural markers related to state borders as well as ethnic boundaries.